cGAS produces a 2′-5′-linked cyclic dinucleotide second messenger that activates STING - Ablasser, Andrea; Goldeck, Marion; Cavlar, Taner; Deimling, Tobias; Witte, Gregor; Röhl, Ingo; Hopfner, Karl-Peter; Ludwig, Janos; Hornung, Veit (Nature (London), 2013)
Cytosolic DNA induces type I interferon via activation of STING; the immediate STING activator is produced by the recently identified DNA sensor cGAS and is shown here to be an unorthodox cyclic dinucleotide harbouring a 2′-5′ linkage between guanosine and adenosine. DNA sensing by cGAS The mechanism of sensing and signalling of cytosolic DNA by the innate immune system is a topic of intense research interest as it is the means by which invading bacteria and viruses are detected. Cytosolic DNA is known to induce type I interferon through activation of the DNA sensor cyclic-GMP-AMP synthetase (cGAS), which catalyses the synthesis of a cyclic dinucleotide which in turn activates a protein known as STING (stimulator of interferon genes). Karl-Peter Hopfner and co-workers present the crystal structures of a C-terminal fragment of cGAS alone, in complex with UTP, and as a DNA–ATP–GTP complex. In a complementary paper [in this issue], Veit Hornung and coworkers show that the product of cGAS is distinct from previously characterized cyclic dinucleotides. Rather it is an unorthodox cyclic dinucleotide with a 2′–5′ linkage between guanosine and adenosine. This two-step synthesis of cGAMP(2′–5′) could be a focus for the development of specific inhibitors for the treatment of autoimmune diseases that engage the cGAS–STING axis. Detection of cytoplasmic DNA represents one of the most fundamental mechanisms of the innate immune system to sense the presence of microbial pathogens 1 . Moreover, erroneous detection of endogenous DNA by the same sensing mechanisms has an important pathophysiological role in certain sterile inflammatory conditions 2 , 3 . The endoplasmic-reticulum-resident protein STING is critically required for the initiation of type I interferon signalling upon detection of cytosolic DNA of both exogenous and endogenous origin 4 , 5 , 6 , 7 , 8 . Next to its pivotal role in DNA sensing, STING also serves as a direct receptor for the detection of cyclic dinucleotides, which function as second messenger molecules in bacteria 9 , 10 , 11 , 12 , 13 . DNA recognition, however, is triggered in an indirect fashion that depends on a recently characterized cytoplasmic nucleotidyl transferase, termed cGAMP synthase (cGAS), which upon interaction with DNA synthesizes a dinucleotide molecule that in turn binds to and activates STING 14 , 15 . We here show in vivo and in vitro that the cGAS-catalysed reaction product is distinct from previously characterized cyclic dinucleotides. Using a combinatorial approach based on mass spectrometry, enzymatic digestion, NMR analysis and chemical synthesis we demonstrate that cGAS produces a cyclic GMP-AMP dinucleotide, which comprises a 2′-5′ and a 3′-5′ phosphodiester linkage >Gp(2′-5′)Ap(3′-5′)>. We found that the presence of this 2′-5′ linkage was required to exert potent activation of human STING. Moreover, we show that cGAS first catalyses the synthesis of a linear 2′-5′-linked dinucleotide, which is then subject to cGAS-dependent cyclization in a second step through a 3′-5′ phosphodiester linkage. This 13-membered ring structure defines a novel class of second messenger molecules, extending the family of 2′-5′-linked antiviral biomolecules.